Invective Metaphors in the Bulgarian Language. An Attempt at a General Characteristic - Dilyana Dencheva (Zeszyty Cyrylo-Metodiańskie)
Invective metaphors constitute a substantial portion of the metaphorical landscape within the Bulgarian language, and likely in other languages as well. This article endeavors to explore Bulgarian invective metaphors from various perspectives, including their vitality, expressiveness, conceptualization schemes, etc. To conduct this research, a questionnaire featuring 20 metaphors was administered to respondents. The collected data revealed two primary categories of metaphors: those with clearly discernible source images and those with obscure source images. Notably, the latter group appears to be transitioning towards historical metaphoricality. The paper proposes a hypothesis elucidating the reasons for that. Additionally, within the framework of the aforementioned aspects, efforts are made to systematize and delineate specific characteristics. Special attention is dedicated to examining Turkisms and insults prevalent not only among individuals, but also between distinct societal fractions, such as football fans.